2020
DOI: 10.1136/bmjopen-2020-038719
|View full text |Cite
|
Sign up to set email alerts
|

Dance for people with chronic respiratory disease: a qualitative study

Abstract: ObjectivesTo explore the experiences and perceived impact on health and well-being related to participation in a dance group for people with chronic respiratory disease (CRD).DesignAn exploratory qualitative study using thematic analysis of semistructured interviews.SettingA community dance group in a UK health centre.ParticipantsConvenience sample of long-term dance group participants.InterventionWeekly community dance sessions designed for people with breathlessness, lasting 75 min, led by a trained communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…As regards the seven studies included in this systematic review, all were published in the last 3 years [ 27 , 28 , 29 , 30 , 31 , 32 ], except one [ 33 ], which was published in 2005. Five studies investigated adults [ 27 , 28 , 29 , 30 , 31 ], whereas one study investigated children [ 32 ], and one final article investigated a population of people aged 17 years old or older [ 28 ]. All the seven studies were conducted in urban areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the seven studies included in this systematic review, all were published in the last 3 years [ 27 , 28 , 29 , 30 , 31 , 32 ], except one [ 33 ], which was published in 2005. Five studies investigated adults [ 27 , 28 , 29 , 30 , 31 ], whereas one study investigated children [ 32 ], and one final article investigated a population of people aged 17 years old or older [ 28 ]. All the seven studies were conducted in urban areas.…”
Section: Resultsmentioning
confidence: 99%
“…Across the studies included in this systematic review, three were conducted in the UK [ 27 , 28 , 29 ], two in the US [ 32 , 33 ], and one in Uganda [ 31 ], and one in Canada [ 30 ]. Four studies employed a pre-/post-quantitative study design [ 28 , 30 , 32 , 33 ], one study employed a mixed-method approach with a pre-/post-quantitative study design and qualitative analysis post-intervention [ 29 ], and two studies gathered qualitative data after the intervention only [ 27 , 31 ]. In terms of sample size, six studies had a sample of fewer than or equal to 20, whereas one study had a sample size of 42 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on Singing for Lung Health (SLH) in the UK suggests participants perceive a range of physical, psychological and social benefits in keeping with our findings 11 18 20 27-29 . Similarly, studies regarding the perceived impacts of dance for people with long-term respiratory conditions in the UK and Canada identify a range of biopsychosocial benefits 10 12 30 . Additionally, an evaluation of SFB Uganda, a singing project for people with CRD in Uganda, provided anecdotal reports that participation was enjoyed 21 , and our findings are broadly in keeping with the evaluation of SFB.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does it influence people at the psychological level and affects people's moods, but also implies the experience of fluid movement, posture and body control, which is considered to be an adjuvant therapy when dealing with stiffness, bradykinesia, and postural instability associated, for example, with Parkinson's disease [ 11 ]. This was determined based on the physiological impact of dance on the body, and as a result of the identification of several studies that showed the effects of dance on the improvement of functional capacity, balance, and strength [ 12 ].…”
Section: Introductionmentioning
confidence: 99%